Alteration in apyrase enzyme attenuated virulence of Shigella flexneri. (February 2016) - BangaSingh, Kirnpal Kaur; Nisha, Mehru; Lau, Hut Yee; Ravichandran, Manickam; Salleh, Mohd Zaki
Abstract: Virulence of Shigella is attributed to the genes presence in chromosome or in the megaplasmid. The apy gene which is located in the megaplasmid of Shigella species encodes for apyrase enzyme, a pathogenesis-associated enzyme causing mitochondrial damage and host cell death. In this study we constructed an apy mutant of Shigella flexneri by insertional activation using a kanamycin resistant gene cassette. The wild type apy gene of S. flexneri 2a was PCR amplified, cloned and mutated with insertion of kanamycin resistant gene cassette ( aph A). The mutated construct ( apy: aph A) was subcloned into a conjugative suicidal vector (pWM91) at the unique Sma 1 and Sac 1 sites. The mutation of the wild apy gene in the construct was confirmed by DNA sequencing. The mutated construct was introduced into wild type S. flexneri 2a by conjugation with Escherichia coli . After undergoing homologous recombination, the wild apy gene was deleted from the construct using the sucrose selection method. Non-functional activity of the apyrase enzyme in the constructed strain by colorimetric test indicated the successful mutation of the apyrase enzyme. This strain with mutated apy gene was evaluated for its protective efficacy using the guinea pig keratoconjunctivitis model. The strain was Sereny negative and it elicited a significant protection following challenge with wild S. flexneri strain. This apy mutant strain will form a base for the development of a vaccine target for shigellosis.